Implementation of Accounting Information Systems Using the Bank Indonesia APIK SI Application in MSMEs - Rachman, Putri Wulandari Hari; Andriani, Sri (Jurnal Akuntansi, 2024)
Purpose –This research aims to analyze and implement the SI APIK application that can assist and manage financial records and financial reports at the company. Design/Methodology/Approach - This research uses a qualitative method with a case study approach, which aims to study and investigate a phenomenon or event for individuals. This research also conducted several data collection techniques such as interviews, observations, and documentation. This method is used to analyze the implementation of the SI APIK application at PT Dinara Indonesia Solusindo. Findings - The results of implementing an accounting information system using the SI APIK application in three subsidiaries of PT Dinara Indonesia Solusindo, namely, Dinara Wooden Heels, Dinara Travelindo, and Calico Jajananku, found that the SI APIK application makes it easier for PT Dinara Indonesia Solusindo to record daily transactions and prepare financial reports according to SAK EMKM, so that owners get financial information in the form of financial statements quickly. Research Limitations/Implications - The limitation of this research is that it only focuses on one company, namely PT Dinara Indonesia Solusindo. The results of this study provide implications so that business owners can implement the SI APIK application to facilitate financial management and decision making. Keywords: Accounting Information System, Financial Statements, SI APIK